In vitro fertilization outcomes after preimplantation genetic testing for chromosomal structural rearrangements comparing fluorescence in-situ hybridization, microarray comparative genomic hybridization, and next-generation sequencing - Chantal B. Bartels, M.D; Reeva Makhijani, M.D; Prachi Godiwala, M.D; Alison Bartolucci, Ph.D; John C. Nulsen, M.D; Daniel R. Grow, M.D; Lawrence Engmann, M.D; Claudio A. Benadiva, M.D., H.C.L.D (Elsevier, 2020)
Objective: To compare in vitro fertilization (IVF) outcomes for preimplantation genetic testing for chromosomal structural rearrangements (PGT-SR) using various testing platforms. Design: Retrospective cohort. Setting: Large academic IVF center. Patient(s): Fifty-one balanced translocation carriers undergoing IVF with PGT-SR who completed a total of 91 cycles, including 31 fluorescence in-situ hybridization (FISH), 24 microarray comparative genomic hybridization (aCGH), and 36 next-generation sequencing (NGS) testing cycles. Intervention(s): PGT-SR. Main Outcome Measure(s): Primary outcome of live-birth rate and secondary outcomes including implantation rate, clinical loss rate, and percentages of normal or balanced, unbalanced, and aneuploid embryos detected. Result(s): There was no statistically significant difference in LBR, though there was a tendency toward a higher LBR for NGS testing (14 of 19, 73.7%) compared with FISH (8 of 18, 44.4%) and aCGH (10 of 20, 50.0%). The implantation rate was statistically significantly higher for NGS (16 of 20, 80.0%) compared with FISH (11 of 25, 44.0%) and aCGH (16 of 30, 53.3%). There was no statistically significant difference in clinical pregnancy losses. There was a lower percentage of normal or balanced embryos with FISH (12.5%) compared with aCGH (23.7%) and with NGS (20.7%). Conclusion(s): This is the first report of PGT-SR outcomes for translocation carriers directly comparing PGT-SR using FISH, aCGH, and NGS. Our findings suggest an improvement in pregnancy outcomes parallel to the advancement in technology and are reassuring for continued use of NGS for this population.